Review on gamification in children computer interaction (CCI) for persona modelling - Nor Haniza binti Mohd Khir; Marina Ismail (Institute of Advanced Engineering and Science, 2019)
Human Computer Interaction (HCI) plays an important role in connecting humans and computers. Many studies conducted to find better alternatives to improve communication between humans and computers. Various frameworks, catalogue and models revised to complement the lack of existing ideas. The growing technology is increasingly being used by not only adults but also children. However, many applications developed do not fully emphasize the use of HCI suitable for children. Thus, Children Computer Interaction (CCI) created to meet the specific needs of children. Yet, there are still many CCI weaknesses being improved to overcome various problems from time to time. One of the ideas presented is through gamification, which is fun and enjoyable in accordance with the nature of the children. Still, the use of gamification is not as simple as adding some game elements into children's apps, but wider to ensure success in achieving the objectives of the developed application. One way that matter is through the use of user-centered design-persona model. So, this paper reviewed the use of current HCI/CCI, gamification and modified the previously proposed design principles in HCI for children into interview questions for data collection which will be analyzed later to create persona model for future work.